The foraging ecology of red deer (Cervus elaphus) in a Mediterranean environment: is a larger body size advantageous? - Bugalho, M N; Milne, J a.; Racey, P a. (Journal of Zoology, 2001)
In Mediterranean environments browse is expected to be a major component of the diet of red deer Cervus elaphus during the summer when most grasses senesce. In this study the hypothesis is tested that, if browse is an essential food resource at this time, the sex with the larger body size may have a greater physical ability to reach the tree canopy and include a higher proportion of browse in its diet. The organic matter digestibility (OMD) and composition of the diet of a population of red deer males and females were measured between July and September, in 1996 and 1997, in an area of Portugal with a Mediterranean type of climate, using the n-alkane technique. Direct observations of animals browsing on tree canopies and shrubs were made also during the same period. The OMD of the diet was signi®cantly different between sexes and between years and was higher in males than females both in 1996 (means sem for males and females, 0.65 and 0.58 0.026, respectively) and 1997 (means for males and females, 0.59 and 0.48 0.045, respectively). The proportion of cork oak Quercus suber in the diet was also signi®cantly different between sexes and between years, with males having a higher proportion of cork oak in their diets in 1996 (males and females, 0.30 and 0.16 0.037, respectively) and 1997 (males and females, 0.41 and 0.23 0.064, respectively). A signi®cantly lower proportion of the herbage layer was found in the diet of males in 1996 (males and females, 0.46 and 0.64 0.048) but not in 1997. The number of observations of males browsing on tree canopies was signi®cantly higher than females. It is concluded that there are differences between sexes in the composition and quality of the diet and that a larger body size may confer advantages in situations where browse is an essential food resource.
Keywords: body-size; browse; cervus elaphus; diet composition; Mediterranean